P70 Developing and celebrating good practice in a hospice setting: equipping a workforce for a changing and uncertain future. (1st October 2013) - Griffith, Sue; Powis, Kate
Abstract : Background: In the current climate of austerity and need to demonstrate that hospices are able to prepare for a changing future of widening access, it is important that hospices take every opportunity to develop practice and ensure the whole workforce is abreast of current thinking. Furthermore, this development must be made explicit to staff and all stakeholders. Having always prided itself on being a centre of excellence, this hospice sought to demonstrate this by being recognised as a practice development unit. Approach: After working with a university to reach first stage accreditation, it was acknowledged that the framework to achieve this was too rigid and costly for a charitable organisation. The existing education and research group was amalgamated with the practice development team to create a Hospice Education And Research and Development (HEARD) group to ensure that every aspect of hospice care follows a practice development approach. Outcomes: The group HEARD offers everyone in the organisation a voice, and a place for their development ideas to be heard. It meets bi-monthly to examine current practice, ideas for research and publication, and to plan a series of learning events to meet changing educational needs of all hospice staff. This plans to generate evidence, develop practice, disseminate good practice, and share best evidence through a journal club, with a focus on developing the workforce and leadership abilities through a largely bottom-up approach. Application: To preserve the academic rigour of the practice development process, eight criteria were created to guide innovation, and the group has a steering committee. Two successful celebration days have now been held to showcase practice developments to stakeholders and staff. An electronic source of educational information has developed from this; the research behind which, as well as other developments, have been published and shared at international conferences.